5(x-14)=4(x-7)

Simple and best practice solution for 5(x-14)=4(x-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-14)=4(x-7) equation:


Simplifying
5(x + -14) = 4(x + -7)

Reorder the terms:
5(-14 + x) = 4(x + -7)
(-14 * 5 + x * 5) = 4(x + -7)
(-70 + 5x) = 4(x + -7)

Reorder the terms:
-70 + 5x = 4(-7 + x)
-70 + 5x = (-7 * 4 + x * 4)
-70 + 5x = (-28 + 4x)

Solving
-70 + 5x = -28 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-70 + 5x + -4x = -28 + 4x + -4x

Combine like terms: 5x + -4x = 1x
-70 + 1x = -28 + 4x + -4x

Combine like terms: 4x + -4x = 0
-70 + 1x = -28 + 0
-70 + 1x = -28

Add '70' to each side of the equation.
-70 + 70 + 1x = -28 + 70

Combine like terms: -70 + 70 = 0
0 + 1x = -28 + 70
1x = -28 + 70

Combine like terms: -28 + 70 = 42
1x = 42

Divide each side by '1'.
x = 42

Simplifying
x = 42

See similar equations:

| 4y+1=56-9 | | 7x-2+3= | | 12=7+3x+1 | | 10-p=-8 | | x^2+10x=-38 | | -3(2x+1)+(3x+2)= | | 1.2+1.5x=5.7 | | 2(d-6)-1=1 | | -2(s-4)-2=2 | | (x+3)(x-2)(x-8)=0 | | n^2+n=22 | | 2y^2-14y+24=0 | | .3x-4x-1=3 | | x+14+x+8=10 | | ex-2=12 | | 2(k-5)-7=1 | | g(p+3)=2x^2+2x+3 | | (4x-3)*(3x-2)= | | 14h-7h=-14 | | 3w+10+2w=5 | | -15/3=x | | -(b--4)=-13 | | 4x^2-21x+22=-4x+4 | | 3j-2j-1=11 | | 24x^2+6x-9=0 | | h(t)=-16t^2+79t+6 | | 42x-14=-17+17x | | 15x-7=5x-13 | | 3r-8=-8 | | v^2+7=0 | | 3x^2+10x+3=19-4x^2+16 | | 6x+2(6x+13)=188 |

Equations solver categories